Multi-session transcutaneous auricular vagus nerve stimulation for Parkinson's disease: evaluating feasibility, safety, and preliminary efficacy - Lench, Daniel H.; Turner, Travis H.; McLeod, Colin; Boger, Heather A.; Lovera, Lilia; Heidelberg, Lisa; Elm, Jordan; Phan, Anh; Badran, Bashar W.; Hinson, Vanessa K. (Frontiers in Neurology, 2023)
Background In pre-clinical animal models of Parkinson's disease (PD), vagus nerve stimulation (VNS) can rescue motor deficits and protect susceptible neuronal populations. Transcutaneous auricular vagus nerve stimulation (taVNS) has emerged as a non-invasive alternative to traditional invasive cervical VNS. This is the first report summarizing the safety, feasibility, and preliminary efficacy of repeated sessions of taVNS in participants with PD. Objectives To evaluate the feasibility, safety, and possible efficacy of taVNS for motor and non-motor symptoms in mild to moderate PD. Methods This is a double-blind, sham controlled RCT (NCT04157621) of taVNS in 30 subjects with mild to moderate PD without cognitive impairment. Participants received 10, 1-h taVNS sessions (25 Hz, 200% of sensory threshold, 500 μs pulse width, 60 s on and 30 s off) over a 2-week period. Primary outcome measures were feasibility and safety of the intervention; secondary outcomes included the MDS-UPDRS, cognitive function and self-reported symptom improvement. Results taVNS treatment was feasible, however, daily in-office visits were reported as being burdensome for participants. While five participants in the taVNS group and three in the sham group self-reported one or more minor adverse events, no major adverse events occurred. There were no group differences on blood pressure and heart rate throughout the intervention. There were no group differences in MDS-UPDRS scores or self-reported measures. Although global cognitive scores remained stable across groups, there was a reduction in verbal fluency within the taVNS group. Conclusions taVNS was safe, and well-tolerated in PD participants. Future studies of taVNS for PD should explore at-home stimulation devices and optimize stimulation parameters to reduce variability and maximize engagement of neural targets.